Analisis Tingkat Upah Riil Pada Setiap Provinsi Di Indonesia Dan Faktor-Faktor Yang Mempengaruhinya - Adwal Hidayatullah Lebi; Muhammad Amir Arham; Boby Rantow Payu (Jurnal Economic Resource, 2026)
This study aims to analyze the influence of economic and social factors on real wage levels across provinces in Indonesia. The variables used in this research include Provincial Minimum Wage (UMP), Economic Growth, Industrial Share, Gross Enrollment Rate in Higher Education (APK-PT), and the Human Development Index (HDI). The study employs panel data from 34 provinces for the period 2019–2023 and uses the Random Effect Model (REM) for panel regression analysis. The results show that UMP, economic growth, industrial share, and APK-PT have a positive and significant effect on real wages. These findings indicate that wage policies, economic growth dynamics, the industrial sector, and improvements in higher education play important roles in enhancing workers’ purchasing power. Conversely, HDI has a negative effect on real wages, suggesting that improvements in human development quality have not yet been fully accompanied by increases in productive employment opportunities across regions. Simultaneously, all independent variables are proven to have a significant effect on real wages. This research highlights that improving real wages across provinces requires synergy in effective wage-setting policies, equitable economic development, strengthening of the industrial sector, and improvements in education and human resource quality to support inclusive and sustainable growth